A strategic alignment framework for the entrepreneurial university. Issue 2 (7th February 2022) - Audretsch, David B.; Belitski, Maksim
ABSTRACT: The Open Innovation in Science literature suggests university knowledge creation should be followed by knowledge dissemination to industry and the public. Although several entrepreneurial university models have been proposed in the literature explaining the role of knowledge production, extant studies generally assume that the elements required by and involved in university outbound innovation are automatically aligned. This conceptual piece introduces the corporate-inspired strategic alignment framework for entrepreneurial universities. In addition, this paper examines the strategic congruence among the individual, organisational and system levels and the functional congruence between knowledge and entrepreneurial capitals. It demonstrates how they can fulfil the increasingly complex role that they must play in science, industry, and society.